Evaluation of Bacterial Profile of Hand and Stethoscope of Doctors with their Knowledge, Attitude and Practice of Hygiene in a Tertiary Teaching Hospital - Rizwan, ASM; Tuly, Sultana Jahan; Suchi, Surovi Era; Ahmed, Tasnim; Nath, Swasti Dev; Paul, Tandra; Shithy, Sumaya Parvin (Medicine Today, 2026)
Introduction: The rapid resurgence of infectious disease severity observed in recent times has multimodal underlying causes. Healthcare associated infection is not an uncommon but often neglected subset of overall infection burden. Physicians play a central role both in conveying and preventing the nosocomial spread. The stethoscope and dominant hand of physicians can transmit infection if their knowledge, attitude and practice pertaining these surfaces are suboptimal. Materials and Methods: We undertook a cross-sectional study to evaluate the knowledge attitude and practice of 70 physicians working in a tertiary teaching hospital related to hand and stethoscope hygiene and their paired sample (n=140) bacteriological profile. Smear sample was collected from each participant’s dominant hand and stethoscope diaphragm to determine the bacterial load and antibiogram. Result: 90% or more physicians know about the role of their hand and stethoscope as a potential mean to spread infection to patients. They also are aware (90%) that consistent hand and stethoscope hygiene can reduce the risk significantly but unfortunately only 18.6% of them were found to clean hands before every patient contact and 61.4% had stated that they clean their stethoscope diaphragm rarely. E. coli was the predominant (55%) organism found in paired hand and stethoscope swabs followed by pseudomonas (8%) and klebsiella (3%). Almost 1 in 3 (33.8%) samples had no growth. 89.5% of all swabs collected from Medicine department had some growth, succeeded by Emergency (75%) and Pediatrics (62.5%). The difference across the departments was significant (p=0.006). Conclusion: There is a vast gap between the knowledge and the practice regarding hand hygiene and stethoscope hygiene among physicians. This can easily be regarded as a blind spot for hospital acquired infection. Strict national guideline and institutional protocol should be implemented to resolve this potential risk. Medicine Today 2026, Vol.38 (1): 103-109